Responsiveness and habituation to repeated sound exposures and pulse trains in blue mussels - Hubert, Jeroen; Booms, Emily; Witbaard, Rob; Slabbekoorn, Hans (Journal of experimental marine biology and ecology, 2022)
Anthropogenic sound has been shown to affect marine animals across taxa. However, bivalves and other invertebrates have received limited attention, and most studies across taxa have focussed on immediate, rather than long-term, effects of sound. Most bivalves adopt a sessile or sedentary lifestyle and are therefore likely to be subject to frequent exposure to the same anthropogenic sounds. For this reason, bivalves are an especially relevant taxonomic group to study with regards to potential long-term effects of sound. In the current study, we examined whether blue mussels (Mytilus edulis) habituate to repeated sound exposures and whether they recover quicker from a single pulse exposure than from a pulse train. We equipped individual mussels with sensors to monitor their valve gape and exposed them to repeated sound playback. We found that mussels responded to sound by partially closing their valves. This response was consistent and repeatable, and decayed over sequential exposures to the same sound stimulus. A stimulus specificity test, meant to determine whether the decayed response could be attributed to habituation or more general sensory adaptation, yielded interesting but ambiguous results. Additionally, we found no differences in the initial response and recovery (time to return to baseline levels) between mussels that were exposed to single pulses and pulse trains. Our results therefore show that mussels reduce responsiveness over sequential exposures and that mussels mostly respond to the onset of a pulse train. Future research is needed to determine whether mussels habituate in situ to actual anthropogenic sound and whether a lack of a behavioural response to repeated sound also implies a lack of other negative effects, such as physiological changes and mortality. •Blue mussels responded to sound by partially closing their valves.•Response strength decayed with repeated exposure.•They responded stronger again to sound of a different frequency in one of the treatments.•Mussels did not respond stronger to a pulse train than to a single pulse.